726 Return to Sport, Patient Reported Outcomes and Satisfaction Following Anterior Cruciate Ligament Reconstruction. (4th May 2021) - Simpson, C; MacDonald, D; Keating, J
Abstract: Introduction: Anterior Cruciate Ligament(ACL) rupture is a common sporting injury. Return to sport is a key objective for patients. The aim of this study was to investigate return to pre-injury level sport at 12- and 24-months post reconstruction and to relate this to types of sport and to patient satisfaction. Method: A questionnaire was developed, piloted, and then completed by 77 patients that had undergone ACL reconstruction between 2013-2016. Results: 30% of patients returned to pre-injury level of sport at 12 months and 43% by 24 months' post ACL reconstruction. There was a significant(P = 0.037) relationship between the type of sports that participants played prior to injury and the return to pre-injury level. Sports that involved jumping, hard pivoting and cutting were associated with a lower rate of return to sport. General health profile of the patients was found to be significantly higher in patients that returned to sport(P = 0.024). There was a significant association with return to sport and higher satisfaction and healthcare experience score(P = 0.001). Conclusions: Patient satisfaction correlated with return to sport. This was inversely related to sports involving jumping, hard pivoting and cutting. Which further illustrates how patient satisfaction post ACL reconstruction was linked to type of sport.